BORROWINGS AS DETERMINANT OF DYNAMICS OF LEXICON UKRAINIAN LANGUAGE OF XVI–XVII CT. - Гриценко, Світлана (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
The language situation in Ukraine in the XVI–XVII centuries by V. Nimchuk definition, was «the most complicated in Europe (if not worldwide)», because the languages «manifested the competition of different ideologies and political-economic systems. Languages were opposing worlds and harbingers of a new world view birth, or the concept of the world» (I. Farion). In the researched period in Ukraine different languages were developed and used: Ukrainian, Church Slavonic, Greek, Latin, Hebraic, Yiddish, Armenian, Turkish, Kipchak-Tatar, Polish, German, Hungarian, Italian, French and others. The result of the language interaction became the lexical borrowings, the amount of which was increased in the XVI–XVII centuries, that was caused by both intralingual and external reasons. It is important to outline the types of changes of the dynamics of Ukrainian lexicon of study period to determine the influence mechanisms of borrowings on the structure of the language-recipient. The purpose. Article is dedicated to explanation of extralingual factors of development of lexicon Ukrainian language of XVI–XVII ct., role of borrowings in this process and their coexistence with native lexic. Changes of lexic of thematical groups of names of persons by their job of kind of business, which were in XVI–XVII ct., are analized. This lexic reflects state of development of craft and industry in Ukraine in period, which being invesigated, and witnesses level of economical, legal, political and cultural development, presence of own and adopted crafts. Research methods. General scientific methods (induction, deduction, analysys, synthesis), special linguistic methods (descriptional, linguo-cultural, systematic-classicifical) and quantity calculation approach are used in this work. Main results of study. Ukrainian literal sources of XVI–XVII ct. prove borrowings from Latin, Greek, Church-Slavic, Polish, German, Italian, French, Hungarian, Romanian, Lituanian, Dutch, Russian, Belorussian, Chekh, Arabian and Turkish languages. These lexems got into Ukrainian language either direct or with mediatory of other languages, most Polish or Chekh, wich was caused by complex lingual or extralingual factors. Scientific novelty of research results. Adoptions as an element of development of Ukrainian lexicon of XVI–XVII ct. made different impact to the development of particular TGL and LSG, which was caused by chain of lingual and extralingual factors and caused multidimention of TGL and non-uniform dencity of outer lexic inside them. Saturation of particular ideographic spheres by borrowings depended on many reasons, in particular, from state of development of corresponding TGL and LSG, actuality of shpere of nomination by itself, existence (and their quantity) of native semantic dublets. Linguists-historicians has different quantity of using of words, remote by time, which allows us to extract particular meanings or their shades from their basement. A linguist is bound to outgoing material, which does not allow him to reach completeness of modelling of lexicon dynamic. Conclusions and specific suggestions of the autor. It’s notices, that using of achievemnts of dialectology, archeology, ethnography, history, folkloristics will allow to contribute significant amends into understanding of specifics of development of Ukrainian language in XVI–XVII ct. Investigation of Ukrainian language realm in diachrony through the prism of literal sources forces an activisation of new lexicographic studies. Creation of array of texts is an important step in modern Ukrainian lexicographic studies, because it supports complex investigation of language material, it’s availability to specialists in different spheres of knowledge